2011
DOI: 10.1002/14651858.cd008288.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Ayurvedic treatments for diabetes mellitus

Abstract: Background-Patients with diabetes frequently use complimentary and alternative medications including Ayurvedic medications and hence it is important to determine their efficacy and safety.Objectives-To assess the effects of Ayurvedic treatments for diabetes mellitus.Search methods-We searched The Cochrane Library (issue 10, 2011), MEDLINE (until 31 August 2011), EMBASE (until 31 August 2011), AMED (until 14 October 2011), the database of randomised trials from South Asia (until 14 October 2011), the database o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 44 publications
0
19
0
1
Order By: Relevance
“…Most likely patients are not using chiropractic care to improve their blood glucose, but rather for treatment of other conditions. It is possible that the herbal therapies used for wellness by these adults are herbs used specifically for diabetes, but there is conflicting evidence or insufficient evidence for efficacy in diabetes …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most likely patients are not using chiropractic care to improve their blood glucose, but rather for treatment of other conditions. It is possible that the herbal therapies used for wellness by these adults are herbs used specifically for diabetes, but there is conflicting evidence or insufficient evidence for efficacy in diabetes …”
Section: Discussionmentioning
confidence: 99%
“…Some evidence exists for the beneficial effects of berberine, cinnamon, coenzyme Q10, mulberry, and vinegar on improving blood sugars and HbA1c, but the evidence for use is conflicting. Cochrane reviews state that there is insufficient evidence to recommend cinnamon, sweet potato, momordica, and ayurvedic treatments for diabetes. In addition, another Cochrane review concluded that although there is some evidence for several Chinese herbal medicines, the findings should be carefully interpreted due to poor methodological quality, limited sample size and a small number of trials.…”
Section: Introductionmentioning
confidence: 99%
“…According to our study results, this population might include younger patients (<60 years of age) with recent onset of diabetes and A1C > 8%. Two recent meta-analyses on herbal treatments for diabetes mellitus urged the need for high-quality large-scale studies that will elucidate the effect of the herbs on glycemic control [13,15]. Although our study provides new information on the hypoglycemic effect of DBCare, we would like to support this proposition.…”
Section: Discussionmentioning
confidence: 66%
“…Of note, the patients in that study were younger than ours (mean age 47.4 years), with a different ethnic background (the majority were Hispanic) and a shorter duration of disease (mean 4.3 years). A recent Cochrane database review on Ayurvedic treatments for diabetes mellitus concluded that Pancreas Tonic did not show a clear hypoglycemic effect [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation